Self-supporting gas membrane bag three-phase interface stable gas diffusion electrode and preparation method and application thereof

CN122877873APending Publication Date: 2026-10-09HARBIN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611364202.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]本发明针对现有气体扩散电极在长期电催化过程中因电润湿导致电解液持续侵入孔道、气体传输通道失效、三相界面塌陷以及催化活性快速衰减等问题,提出了一种具有自支撑气膜囊的纳米限域气体扩散电极及其构筑方法

Benefits of technology

本发明首次提出基于纳米限域自支撑气膜囊的三相界面稳定策略,推动氧还原反应界面由传统的被动润湿抵抗向主动界面稳定实现机制性转变。通过在碳纳米管内构建具有氧气定向捕获与富集功能的纳米限域孔道,显著延长氧气分子在催化界面的停留时间,从而在供氧波动条件下仍能维持持续、高效的氧供给能力。同时,电解液以受限薄液膜形态浸润孔道,在保证离子高效传输的前提下,有效抑制孔道整体淹没,突破传统超疏水结构在气-液传输协同方面的技术瓶颈。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122877873A_ABST
    Figure CN122877873A_ABST
Patent Text Reader

Abstract

The application discloses a self-supporting gas film bag three-phase interface stable gas diffusion electrode and a manufacturing method and application thereof, and belongs to the field of organic pollutant degradation.The application aims at the problems of existing gas diffusion electrodes, such as continuous invasion of electrolyte into the pore channel, failure of gas transmission channel, collapse of three-phase interface and rapid decay of catalytic activity, caused by electrowetting in a long-term electro-catalysis process.The application forms a stable nanoscale gas storage cavity by constructing a porous framework with oxygen capturing capacity in-situ in a carbon nanotube, realizes continuous enrichment and slow release of oxygen in the pore channel, and thus constructs a stable gas-liquid-solid three-phase reaction interface.The application can actively maintain a thin liquid film wetting state under the condition of electrowetting, instead of simply repelling liquid by relying on a super-hydrophobic surface in the traditional technology, and fundamentally solves the problem of mutual restriction between gas transmission and ion transmission.The application is used for degrading sulfamethoxazole, acetaminophen, tetracycline, sulfadiazine and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organic pollutant degradation, specifically, it relates to a self-supporting gas membrane bag three-phase interface stable gas diffusion electrode, its preparation method and application. Background Technology

[0002] Gas diffusion electrodes, due to their ability to achieve efficient coupling between gas, liquid, and solid catalytic interfaces, have been widely used in electro-Fenton and electrocatalytic oxygen reduction fields. However, during long-term operation, electrowetting caused by the electric field can lead to the gradual intrusion of electrolyte into the electrode's internal channels, causing the original gas transport network to be gradually replaced by liquid, resulting in electrode submersion. Once the gas diffusion channels fail, oxygen cannot be continuously delivered to the catalytically active sites, leading to a rapid decrease in local oxygen concentration, disruption of the three-phase reaction interface, and consequently, a reduction in the oxygen reduction reaction rate, a decrease in the generation of reactive oxygen species, and a rapid decline in the electrode's catalytic performance. This problem has become a key technical bottleneck restricting the long-term stable operation of gas diffusion electrodes.

[0003] To address the aforementioned issues, existing technologies primarily enhance the hydrophobicity of materials by constructing superhydrophobic surfaces or optimizing surface micro / nano structures to delay electrolyte penetration into the pores. However, these solutions essentially still focus on preventing liquid from entering the electrode interior. While this can mitigate the flooding process to some extent, it also inhibits electrolyte penetration and ion transport within the pores, which is detrimental to Fe... 2+ / Fe 3+ The cycling and charge transfer processes affect the efficiency of electrocatalytic reactions. Furthermore, with the continuous enhancement of electrowetting, relying solely on surface hydrophobicity is insufficient to prevent the eventual failure of gas channels, and the long-term stability of the electrode remains inadequate.

[0004] Furthermore, some studies have attempted to compensate for oxygen deficiency by increasing oxygen supply flow rate, enhancing external convection, or continuous bubbling. However, these methods are highly dependent on continuous external oxygen supply, consume a lot of energy, and the externally input oxygen is difficult to retain effectively inside the electrode. Under complex water quality conditions and during long-term operation, problems such as oxygen loss and three-phase interface instability still easily occur. Existing technologies mostly focus on preventing liquid from entering the electrode, while paying less attention to the active storage, continuous maintenance, and dynamic control of the gas phase in the channels. A stable three-phase interface control mechanism that can take into account gas transport, liquid wetting, and electron transfer has not yet been established.

[0005] Therefore, how to construct a novel electrode structure that can maintain gas storage capacity and achieve continuous oxygen supply in order to stably maintain the three-phase reaction interface remains an important technical problem that needs to be solved in this field. Summary of the Invention

[0006] This invention addresses the problems of electrowetting in existing gas diffusion electrodes during long-term electrocatalysis, including continuous electrolyte intrusion into the pores, failure of gas transport channels, collapse of the three-phase interface, and rapid decline in catalytic activity. It proposes a nano-confined gas diffusion electrode with a self-supporting gas membrane and its construction method. This invention constructs a porous framework with oxygen-capturing capabilities in situ within carbon nanotubes, forming a stable nanoscale gas storage cavity. This enables the continuous enrichment and slow release of oxygen within the pores, thereby constructing a stable gas-liquid-solid three-phase reaction interface. This invention actively maintains the wetted state of the thin liquid film under electrowetting conditions, rather than relying on the simple repulsion of liquid by superhydrophobic surfaces as in traditional techniques, fundamentally solving the problem of mutual constraints between gas transport and ion transport.

[0007] To address the aforementioned technical problems, the present invention adopts the following technical solution: The purpose of this invention is to provide a method for preparing a self-supporting gas film bladder three-phase interface stable gas diffusion electrode, comprising the following steps: Step 1: Preparation of carbon nanotube solution: Add multi-walled carbon nanotubes to concentrated nitric acid and ultrasonically disperse until uniform (takes about 1 hour). Heat and stir under reflux in an oil bath. After the reaction is complete, wash with deionized water until neutral. Vacuum dry and then freeze dry to obtain carbon nanotubes with open ends. Take a certain amount and add it to deionized water and ultrasonically disperse until uniform to obtain carbon nanotube solution. Step 2: Preparation of boron-modified carbon nanotube conductive framework: Boric acid was dissolved in anhydrous ethanol to obtain a boric acid solution. The boric acid solution and carbon nanotube solution were added to acetone and mixed until homogeneous. The mixture was then sonicated to allow the boric acid to enter the pores of the carbon nanotubes. The outer walls of the carbon nanotubes were then washed by vacuum filtration, and the solvent was removed in a 353.2 K vacuum oven. The mixture was then dried at 2 K·min under a nitrogen atmosphere. -1 The temperature was raised to 1273.2 K and held for 2 hours. After cooling, the tubes were washed alternately with anhydrous ethanol and ultrapure water and then dried under vacuum to obtain boron-modified carbon nanotubes (BCNTs), which are the conductive frameworks of boron-modified carbon nanotubes. Step 3: Preparation of slurry: Boron-modified carbon nanotubes (BCNTs) are ultrasonically dispersed in anhydrous ethanol, and polytetrafluoroethylene dispersion is added under vigorous stirring. The mixture is heated and stirred until homogeneous to obtain the slurry. Step 4: Preparation of basic gas diffusion membrane: Clean the stainless steel mesh, immerse it in polytetrafluoroethylene suspension, take it out and dry it, coat the slurry evenly on one side of the stainless steel mesh, anneal it to obtain the basic gas diffusion membrane. Step 5: Electrode preparation: Dissolve hexadecyltrimethylammonium bromide, ferric chloride hexahydrate, and acetic acid in deionized water and stir until homogeneous (approximately 1 hour). Add annealed stainless steel mesh and 2-aminoterephthalic acid and continue stirring for at least 2 hours to allow the precursor to enter the pores of the carbon nanotubes under capillary action. Perform a hydrothermal reaction, cool, wash with ethanol, and vacuum dry to obtain an oxygen-trapping composite membrane confined within the pores. This yields a self-supporting gas membrane bladder three-phase interface stable gas diffusion electrode, denoted as RF-in-BCNT.

[0008] To further specify, in step 1, the mass fraction of concentrated nitric acid is 68%.

[0009] Further specifying, in step 1, the ratio of the mass of multi-walled carbon nanotubes to the volume of concentrated nitric acid is (2-4) g: 200 mL.

[0010] Further specifying, in step 1, the ultrasonic frequency is 40 kHz and the ultrasonic power is 300 W.

[0011] Further specifying, in step 1, the oil bath temperature is 120℃-140℃, preferably 130℃, and the reflux time is at least 14 hours.

[0012] Further specifying, in step 1, vacuum drying is performed at 60°C for at least 12 hours.

[0013] Further specifying, in step 1, the freeze-drying is carried out at -45°C for at least 48 hours.

[0014] Further specifying, in step 1, the ratio of carbon nanotubes with open ends to deionized water is 0.2 g: (10-20) mL.

[0015] Further specifying, in step 2, the mass ratio of boric acid to the volume of anhydrous ethanol is 1.5 g : 20 mL, and the mass fraction of anhydrous ethanol is 99%.

[0016] Further specifying, in step 2, the mass ratio of boric acid to carbon nanotubes with open ends is 0.2 ∶ (0.3-3), preferably 0.2 ∶ 1.5.

[0017] Further specifying, the volume ratio of boric acid solution to acetone in step 2 is 1:(1-2).

[0018] To further specify, in step 2, the washing is repeated 5-6 times.

[0019] Further specifying, in step 2, vacuum drying is performed at 60°C for at least 6 hours.

[0020] In step 2, the capillary action, ultrasound, and stirring of carbon nanotubes are used to allow the boric acid precursor to enter the pores of the carbon nanotubes.

[0021] Step 3: Preparation of slurry: Boron-modified carbon nanotubes (BCNTs) are ultrasonically dispersed in anhydrous ethanol, and polytetrafluoroethylene dispersion is added under vigorous stirring. The mixture is heated and stirred until homogeneous to obtain the slurry. Further specifying, in step 3, the mass ratio of boron-modified carbon nanotubes (BCNTs) to the volume ratio of anhydrous ethanol is 25 mg:(10-20) mL. Further specifying, in step 3, the mass ratio of boron-modified carbon nanotubes (BCNT) to polytetrafluoroethylene is 5:3.

[0022] Further specifying, in step 3, the vigorous stirring speed is 1000 rpm–1500 rpm.

[0023] Further specifying, in step 3, the concentration of the polytetrafluoroethylene dispersion is 60 wt%.

[0024] Further specifying, in step 3, heating is performed at 70°C.

[0025] Further specifying, in step 4, the stainless steel mesh serving as the support layer has a mesh size of 30-100 mesh; it provides mechanical strength and electronic conduction pathways; the stainless steel mesh is preferably 50 mesh, but a metal mesh with similar support function can also be used depending on the membrane thickness and equipment size. A conductive porous functional layer is located on one side of the stainless steel mesh. This functional layer uses fractured carbon nanotubes or their boron-modified products as the main conductive framework and contains a polytetrafluoroethylene binder phase. An amino-containing network framework is located on the surface of the carbon nanotube pores. This network framework is formed in situ under hydrothermal conditions by iron salts, aminoterephthalic acid, and an acid modifier; the network framework is not mainly distributed on the outer surface of the carbon nanotubes, but rather distributed in a confined manner within the pores. The composite membrane has interconnected gas channels, electronic conduction pathways, and aqueous ion transport pathways, forming a gas-liquid-solid three-phase reaction region during operation.

[0026] Further specifying, in step 4, the mass fraction of the polytetrafluoroethylene suspension is 5%.

[0027] Further specifying, in step 4, the BCNT loading reaches 12.5 mg·cm³. 2 .

[0028] Further specifying, in step 4, annealing is performed at 350°C.

[0029] Further specified, the sample is immersed in a polytetrafluoroethylene suspension for at least 30 minutes.

[0030] Further specifying, in step 5, the ratio of hexadecyltrimethylammonium bromide, ferric chloride hexahydrate, and deionized acetic acid is 54 mg: 200 mg: 68 mg: 0.3 mL: 15 mL.

[0031] Further specifying, in step 5, the mass ratio of hexadecyltrimethylammonium bromide to 2-aminoterephthalic acid is 54 mg: 68 mg.

[0032] Further specifying, in step 5, the hydrothermal reaction is carried out at 110°C for at least 24 hours.

[0033] Further specifying, in step 5, the hydrothermal reaction is carried out in a hydrothermal reactor lined with polytetrafluoroethylene.

[0034] Another objective of this invention is to provide a self-supporting gas membrane bladder three-phase interface stable gas diffusion electrode prepared by any of the above methods.

[0035] Further, its application as a cathode in the degradation of organic pollutants is defined.

[0036] The composite membrane described in this invention is applicable to a wide range of typical organic pollutants, including but not limited to sulfamethoxazole, acetaminophen, tetracycline, sulfadiazine, phenolic compounds, naproxen, carbamazepine, atrazine, and chloramphenicol. Furthermore, the composite membrane of this invention is also suitable for treating actual water samples containing natural organic matter or inorganic salts, as well as nanofiltration concentrates produced by processes such as reverse osmosis.

[0037] Furthermore, the present invention also provides an electro-Fenton water treatment method for degrading organic pollutants in water, comprising the following steps: The composite membrane prepared by any of the above methods is used as the cathode. One side of the cathode is immersed in a reaction solution containing organic pollutants, and the other side of the cathode is in contact with oxygen or air. A DSA electrode is used as the anode. Supporting electrolyte and ferrous salt are added to the reaction solution and the pH is adjusted to acidity to oxidize and degrade organic pollutants.

[0038] Furthermore, the reactor can be a diaphragmless electrolyzer or a continuous flow reactor with the same gas-liquid-solid contact relationship.

[0039] Furthermore, the distance between the anode and cathode is specified to be 5 mm to 20 mm.

[0040] Further specifying, the electrolyte is sodium sulfate, and the amount of sodium sulfate used is 0.1-0.01 mol·L⁻¹. -1 .

[0041] Further specifying, the pH value is adjusted using dilute sulfuric acid, wherein the concentration of the dilute sulfuric acid is 2 mol·L⁻¹. -1-5 mol·L -1 .

[0042] Further specifying, the ferrous salt is ferrous sulfate, and the amount of ferrous sulfate used is 0.1 mmol·L⁻¹. -1 .

[0043] This invention utilizes nanoscale confined spaces for selective adsorption and local enrichment of oxygen, thereby forming a gas film bladder structure with stable internal pressure within the pores. Based on this, an electric field is applied to allow the electrolyte to enter the pores in the form of a confined thin liquid film. This process ensures the preservation of Fe... 2+ / Fe 3+ The cyclic regeneration of the redox couple and the unobstructed electron transport pathway prevent the pores from being completely submerged by the electrolyte, thus avoiding the loss of the gas-liquid-solid three-phase interface. Simultaneously, the stable gas film within the pores continuously supplies oxygen to the catalytically active sites, effectively prolonging the residence time of oxygen molecules, increasing local oxygen partial pressure and oxygen utilization, thereby ensuring the stable progress of the oxygen reduction reaction and the generation of reactive oxygen species. Through this synergistic mechanism, this invention transforms the traditional irreversible pore submersion process into a controllable, confined thin-film wetted state, significantly improving the electrode's stability during long-term operation and its electrocatalytic degradation efficiency for pollutants.

[0044] Sulfamethoxazole was used as a model pollutant for treatment. Oxygen was captured and enriched in the cathode channel, and oxygen was reduced to generate H2O2. H2O2 reacted with ferrous ions to form hydroxyl radicals, and at the same time, reactive oxygen species such as singlet oxygen were generated, thereby oxidizing and degrading organic pollutants in the water.

[0045] Compared with the prior art, the present invention has the following beneficial effects: This invention proposes for the first time a three-phase interface stabilization strategy based on a nano-confined self-supporting gas membrane, driving a mechanistic shift in the oxygen reduction reaction interface from traditional passive wetting resistance to active interface stabilization. By constructing nano-confined channels with directional oxygen capture and enrichment functions within carbon nanotubes, the residence time of oxygen molecules at the catalytic interface is significantly extended, thus maintaining a continuous and efficient oxygen supply capacity even under fluctuating oxygen supply conditions. Simultaneously, the electrolyte wets the channels in a confined thin liquid film form, effectively suppressing overall channel submersion while ensuring efficient ion transport, overcoming the technical bottleneck of traditional superhydrophobic structures in gas-liquid transport synergy.

[0046] Compared to conventional BCNT membranes and RF-out-BCNT membranes, this invention does not simply rely on increased specific surface area, but rather regulates the synergistic distribution of oxygen, electrolytes, and electrons within the same reaction region through an intrapore-confined structure. The amino-based network framework, positioned on the inner wall of the carbon nanotubes, increases the local oxygen concentration within the pores and prolongs its residence time, maintaining high H₂O₂ generation kinetics even with a brief interruption of external oxygen supply. Simultaneously, the intrapore structure slows down complete aqueous phase intrusion, prevents gas channels from being blocked by liquid, and preserves the thin liquid film required for ion transport.

[0047] The composite membrane of this invention uses a stainless steel mesh as a support and polytetrafluoroethylene as a binder phase. The preparation process is clear, and the resulting membrane can be directly used as a cathode without additional coating. In the electro-Fenton reaction, RF-in-BCNT showed a significantly better initial removal rate of sulfamethoxazole than BCNT and RF-out-BCNT; at an oxygen flow rate of 0.5 mL / min... -1 At that time, it takes about 7 minutes to almost completely remove it. Further oxygen deprivation experiments showed that the apparent H2O2 formation rate constant of BCNT decreased from 2.48 min. - ¹ decreased to 2.02 min -1 RF-out-BCNT is 5.77 min -1 Reduced to 5.13 min -1 RF-in-BCNT, on the other hand, is 7.48 min. -1 Up to 7.82 min -1 This clearly demonstrates that the confined structure within the pores has a significant ability to delay oxygen release and maintain the reaction.

[0048] The composite membrane of this invention does not rely on light and can use oxygen or air as an oxygen source. It is suitable for intermittent electrolyzers and continuous flow membrane electrode reactors, and has good practicality and versatility.

[0049] For a deeper understanding of the features and technical content of this invention, please refer to the accompanying detailed description and drawings. It should be noted that the drawings are provided for illustrative purposes only and are not intended to limit the scope of the invention. Attached Figure Description

[0050] Figure 1 This is a SEM comparison of the surfaces of the RF-out-BCNT (ab) membrane and the RF-in-BCNT (cd) membrane; Figure 2 The SMX degradation effects of BCNT, RF-out-BCNT, and RF-in-BCNT under different oxygen fluxes are shown in (a); and at oxygen fluxes of 0 mL·min⁻¹, the degradation effects are shown in (a). -1 (b) 2.5 mL·min -1 (c) and 5 mL·min -1(d) Degradation efficiency; Figure 3 This is a schematic diagram of a continuous flow catalytic unit: 1—water storage container, 2—liquid pump, 3—membrane reactor, 4—outlet container; Figure 4 This refers to the degradation efficiency of the SMX nanofiltration concentrate after treatment by this continuous flow catalytic unit; Figure 5 It is the degradation efficiency of deionized water nanofiltration concentrate after being treated by this continuous flow catalytic unit; Figure 6 This refers to the degradation efficiency of RF-in-BCNT for 12 typical organic pollutants. Detailed Implementation

[0051] The present invention will be described in detail below with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but should not be considered as limiting the present invention. It should be noted that those skilled in the art can make several modifications and improvements without departing from the concept of the present invention. These all fall within the protection scope of the present invention.

[0052] Example 1: The preparation method of the self-supporting gas film bladder three-phase interface stable gas diffusion electrode in this example is carried out according to the following steps: Step 1: Preparation of carbon nanotubes with open ends and carbon nanotube solution: Step 1.1: Preparation of carbon nanotubes with open ends: Take 2 g of multi-walled carbon nanotubes and add them to 200 mL of 68% nitric acid. After sonicating for 1 hour at room temperature, ultrasonic frequency of 40 kHz and ultrasonic power of 300 W, stir and reflux at 200 rpm in an oil bath at 130℃ for 14 hours. After cooling, wash with deionized water until the pH value is 7, vacuum dry at 60℃ for 12 hours, and then freeze dry at -45℃ for 48 hours to obtain carbon nanotubes with open ends. Step 1.2, Preparation of carbon nanotube solution: Take 0.2 g of open-ended carbon nanotubes and place them in 20 mL of deionized water. Sonicate for 1 hour at an ultrasonic frequency of 40 kHz and an ultrasonic power of 300 W to obtain a carbon nanotube solution.

[0053] The multi-walled carbon nanotubes have a diameter of 10 nm-20 nm and a length of 0.5 μm-2 μm.

[0054] Step 2, Preparation of boron-modified carbon nanotubes (BCNTs): 1.5 g of boric acid was dissolved in 20 mL of 99% ethanol to obtain a boric acid solution. The boric acid solution and carbon nanotube solution were then mixed in 40 mL of acetone and sonicated at a frequency of 40 kHz and a power of 300 W for 4 hours. After washing the outer wall through vacuum filtration, the nanotubes were vacuum dried at 80 °C for 12 hours. Subsequently, the nanotubes were dried under a nitrogen atmosphere at 2 °C / min. -1 The temperature was raised to 1000 ℃ and held for 2 hours. After cooling, the tubes were washed 6 times alternately with anhydrous ethanol and ultrapure water. They were then vacuum dried at 60 ℃ for 6 hours to obtain boron-modified carbon nanotubes, denoted as BCNT.

[0055] Step 3, Preparation of slurry: 25 mg of boron-modified carbon nanotubes (BCNT) were ultrasonically dispersed in 20 mL of anhydrous ethanol and ultrasonicated for 10 minutes. 25 mg of 60 wt% polytetrafluoroethylene dispersion was added at 70℃ and 1200 rpm. The mixture was heated and stirred until homogeneous to obtain the slurry. Step 4: Preparation of the CNT-based gas diffusion membrane: After cleaning a 50-mesh stainless steel mesh three times each with deionized water and anhydrous ethanol, it was immersed in a 5% (w / w) polytetrafluoroethylene (PTFE) suspension for 30 minutes. It was then removed and dried at room temperature. The slurry was then evenly coated onto one side of the stainless steel mesh until the BCNT loading reached 12.5 mg·cm⁻¹. -2 The BCNT basic gas diffusion membrane was obtained by annealing at 350℃ for 60 minutes.

[0056] Step 5: Preparation of the RF-in-BCNT composite membrane: 54 mg of cetyltrimethylammonium bromide, 200 mg of ferric chloride hexahydrate, and 0.3 mL of acetic acid were dissolved in 15 mL of deionized water and stirred at 600 rpm for 1 hour. Then, the BCNT basic gas diffusion membrane prepared in step 4 and 68 mg of 2-aminoterephthalic acid were added, and stirring was continued for 2 hours. The mixture was then transferred to a polytetrafluoroethylene-lined hydrothermal reactor and reacted at 110 °C for 24 hours. After cooling, the mixture was washed 5 times with ethanol and dried under vacuum overnight at 80 °C to obtain the RF-in-BCNT composite membrane.

[0057] In this embodiment, hexadecyltrimethylammonium bromide is used as a pore entry aid to enable the iron-containing precursor and aminoterephthalic acid to enter the inner pores of the carbon nanotubes and grow in situ near the inner wall.

[0058] The RF-in-BCNT composite membrane is used for electro-Fenton degradation, specifically through the following steps: The RF-in-BCNT composite membrane is used as the cathode. The composite membrane with a size of 20 mm × 20 mm is immersed in the reaction solution, so that the other side of the membrane is connected to oxygen or air. The DSA electrode with a size of 35 mm × 20 mm × 0.1 mm is used as the anode. The distance between the anode and the cathode is preferably 10 mm.

[0059] Add 0.05 mol·L⁻¹ to a 60 mL diaphragm-free electrolyzer. -1 Sodium sulfate solution (supporting electrolyte), with dilute sulfuric acid (3 mmol·L⁻¹). -1 Adjust the pH to 3. Use the RF-in-BCNT composite membrane as the cathode and the DSA electrode as the anode, with an electrode spacing of 10 mm; introduce oxygen into the gas side of the cathode at a flow rate of 0.5 mL / min. -1 The solution was stirred at a speed of 600 r·min. -1 Add 0.1 mmol·L -1 Ferrous sulfate and 10 μmol·L -1 Sulfamethoxazole. During electrolysis, oxygen is reduced at the cathode to generate H2O2. H2O2 participates in the Fenton reaction of ferrous ions, producing hydroxyl radicals and other reactive oxygen species, which oxidize and degrade sulfamethoxazole.

[0060] Under the same conditions, BCNT and RF-out-BCNT were used as cathodes for control. RF-in-BCNT was used at 0.5 mL / min. 1 The degradation rate is fastest when oxygen is supplied at low flow rates, reaching near-complete removal in about 7 minutes.

[0061] Comparative Example 1 differs from Example 1 in that the mass fraction of nitric acid is 38%, and the carbon nanotubes are prepared by reflux at 109°C for 14 hours. All other raw materials, amounts, and preparation steps are the same as in Example 1.

[0062] Comparative Example 2: Preparation of the RF-out-BCNT control membrane: Except for replacing hexadecyltrimethylammonium bromide with Pluronic F127, the other raw materials, amounts and preparation steps were the same as in Example 1, and the RF-out-BCNT control membrane was obtained.

[0063] Because the F127 molecule is relatively large, it is difficult for it to enter the pores of carbon nanotubes. The amino network framework mainly grows on the outer surface of the carbon nanotubes, resulting in a structure different from RF-in-BCNT. Therefore, the performance improvement of this invention comes from the confined structure within the pores, rather than simply increasing the amount of deposition on the outer surface.

[0064] The following experiments were used to verify the effectiveness of the invention. Experiment 1: Oxygen Maintenance Experiment under Oxygen Deprivation Conditions Oxygen was continuously introduced for 0–10 minutes after the start of the electro-Fenton reaction, and the oxygen supply was stopped for 10–20 minutes. The apparent rate constants of H2O2 generation in the BCNT, RF-out-BCNT, and RF-in-BCNT systems were recorded. The rate constant of BCNT was 2.48 min. -1 Reduced to 2.02 min -1 ;RF-out-BCNT from 5.77 min -1 Reduced to 5.13 min -1 ;RF-in-BCNT from 7.48 min -1 Increased to 7.82 min -1 This result demonstrates that the oxygen-trapping structure within the RF-in-BCNT pores can continue to release and utilize oxygen within the pores even after external oxygen supply has ceased.

[0065] The prepared composite membrane was observed using a scanning electron microscope (e.g.) Figure 1 (As shown). The outer surface of RF-out-BCNTs exhibits more pronounced granular or sheet-like RF structures, while the outer surface of RF-in-BCNTs remains predominantly composed of interwoven carbon nanotube structures, with no large amounts of RF particles covering the outer wall. This difference is related to the varying abilities of surfactant molecules to enter the CNT cavity during preparation, indicating that the main difference between the two samples is not simply an increase in RF loading, but rather the different positions of the RF inside and outside the CNT.

[0066] Experiment 2: Oxygen Confinement and Activation Experiment To investigate the effect of external oxygen supply on structural performance, an O2 flow-dependent experiment was also conducted. Figure 2 The SMX degradation effect of BCNT, RF-out-BCNT, and RF-in-BCNT under different oxygen fluxes. Figure 2 (a) Comparison of oxygen flux of 0.5 mL·min -1 and 2.5 mL·min -1 The degradation efficiency at 2.5 mL·min. -1 Under the given conditions, all three electrodes exhibited high degradation efficiency; when the oxygen flux was reduced to 0.5 mL·min -1 At that time, the degradation efficiency of BCNT and RF-out-BCNT decreased significantly, while RF-in-BCNT remained at a high level.

[0067] Figure 2 (b) shows the degradation curves when no oxygen is introduced. The degradation efficiency of RF-in-BCNT is always higher than that of RF-out-BCNT and BCNT. Figure 2(c) represents an oxygen flux of 2.5 mL·min -1 The degradation curves at different times show that the degradation efficiency of all three electrodes increases rapidly with increasing reaction time and gradually approaches complete removal. Figure 2 (d) represents an oxygen flux of 5 mL·min -1 The degradation curves at different times showed that all three electrodes exhibited a gradually increasing degradation trend. Overall, RF-in-BCNT still demonstrated good SMX degradation performance under conditions of no oxygen inlet and low oxygen flux.

[0068] Experiment 3: Verification Experiment of Long-Term Continuous Operation Performance of Continuous Flow Reactor To verify whether the composite membrane can transition from batch reaction to continuous processing, a continuous flow catalytic unit was further constructed. This unit mainly includes an influent storage container, a delivery pump, a membrane reactor, and an effluent container (such as...). Figure 3 (As shown). The water to be treated is continuously fed into the reactor by a pump. An RF-in-BCNT membrane is installed inside the reactor as the cathode. O2 or air is introduced into the gas side of the membrane, while the aqueous phase flows continuously through the liquid side of the membrane and completes the electro-Fenton reaction within the reactor. The treated water is continuously discharged from the outlet. The gas flow rate and liquid flow rate can be adjusted separately to maintain the gas-liquid-solid three-phase interface inside the membrane without significantly increasing external agitation.

[0069] In the continuous flow experiment, the liquid flow rate was approximately 2 mL·min. -1 The membrane side is supplied with either O2 or air, with a gas flow rate of approximately 0.5 mL / min. -1 In the simulated continuous wastewater treatment process, a concentration of 0.5 mL / min was used. -1 At O2, the SMX removal rate remained close to complete throughout the approximately 50-hour test cycle; even after switching the gas supply to air, the SMX removal rate remained above 95%. Continuous flow curves showed that RF-in-BCNT maintained high SMX removal efficiency in both deionized water and nanofiltration concentrate during continuous operation, and no irreversible performance degradation occurred under gas switching, pH changes, and short-term load variations.

[0070] In real-world complex water bodies, the SMX removal rate of nanofiltration concentrate reached approximately 96.6% within 10 minutes, indicating that the composite membrane has a certain adaptability to high salinity backgrounds and natural organic matter. During long-term continuous flow operation, the stability under air conditions was actually better than under pure oxygen conditions, possibly related to the lower oxygen partial pressure and the influence of CO2 in the air on the carbonate buffer system of the nanofiltration concentrate. By controlling the gas and liquid flow rates, a balance can be achieved between oxygen supply, anti-electrowetting, and pH stability. Therefore, the continuous flow experiment also demonstrates that the membrane exhibits good long-term operational stability and a certain degree of adaptability to complex water bodies.

[0071] Experiment 4: Achieving Removal Efficiency for Different Organic Pollutants For sulfamethoxazole (SMX), acetaminophen (PCM), tetracycline (TC), sulfadiazine (SMT), salicylic acid (SA), bisphenol A (BPA), p-hydroxybenzoic acid (HBA), naproxen (NPX), carbamazepine (CBZ), atrazine (ATZ), benzoic acid (BA), and chloramphenicol (CAP), the method described in Example 1 was used. The results were as follows. Figure 6 As shown in the figure, RF-in-BCNT exhibits good degradation effects on organic pollutants with different structural types. The removal efficiency for pollutants such as SMX, PCM, TC, SMT, SA, BPA, HBA, and NPX reaches approximately 90% or even near-complete removal. It also maintains high degradation efficiency for pollutants with higher structural stability, such as CBZ, ATZ, BA, and CAP, with an overall removal rate of approximately 55%–90%. These results indicate that the RF-in-BCNT composite membrane prepared in this invention has a wide range of applicable pollutants and can effectively degrade different types of pharmaceuticals, personal care products, and industrial organic pollutants.

[0072] The specific embodiments of the present invention have been described in detail above. It should be noted that the present invention is not limited to the specific embodiments described above. Various modifications or alterations can be made by those skilled in the art without departing from the scope of protection defined by the claims, and all such modifications or alterations fall within the scope of the present invention.

Claims

1. A method for preparing a self-supporting gas film bladder three-phase interface stable gas diffusion electrode, characterized in that, Includes the following steps: Step 1: Add multi-walled carbon nanotubes to concentrated nitric acid, ultrasonically disperse until uniform, heat and stir under reflux in an oil bath, wash with deionized water until neutral after the reaction is complete, vacuum dry and then freeze dry to obtain carbon nanotubes with open ends, take a certain amount and add to deionized water and ultrasonically disperse until uniform to obtain carbon nanotube solution. Step 2: Dissolve boric acid in anhydrous ethanol to obtain a boric acid solution. Add the boric acid solution and carbon nanotube solution to acetone and mix until homogeneous. Use sonication to allow the boric acid to enter the pores of the carbon nanotubes. Then, wash the outer wall of the carbon nanotubes through vacuum filtration, remove the solvent, calcine under an inert gas atmosphere, cool, wash alternately with anhydrous ethanol and ultrapure water, and vacuum dry to obtain boron-modified carbon nanotubes. Step 3: Disperse boron-modified carbon nanotubes ultrasonically in anhydrous ethanol, add polytetrafluoroethylene dispersion under vigorous stirring, heat and stir until uniform to obtain slurry; Step 4: Clean the stainless steel mesh, immerse it in a polytetrafluoroethylene suspension, remove and dry it, coat the slurry evenly on one side of the stainless steel mesh, and anneal it. Step 5: Dissolve hexadecyltrimethylammonium bromide, ferric chloride hexahydrate, and acetic acid in deionized water and stir for 1-2 hours. Add annealed stainless steel mesh and 2-aminoterephthalic acid and continue stirring for at least 2 hours for hydrothermal reaction. After cooling, wash with ethanol and vacuum dry to obtain the electrode.

2. The method according to claim 1, characterized in that, In step 1, the diameter of the multi-walled carbon nanotubes is 10nm–20nm and the length is 0.5μm–2μm; the mass fraction of concentrated nitric acid is 68%; the oil bath temperature is 120℃–140℃; the nanotubes are vacuum dried at 60℃ and freeze-dried at -45℃; and the ratio of open-end carbon nanotubes to deionized water is 0.2 g:(10-20) mL.

3. The method according to claim 1, characterized in that, In step 2, the mass ratio of boric acid to anhydrous ethanol is 1.5 g: 20 mL, and the mass ratio of boric acid to carbon nanotubes with open ends is 0.2: (0.3-3). The solvent is removed by heating at 80 °C; the inert gas is nitrogen, and calcination is carried out at 2 °C / min. -1 Rapidly heat to 1000℃ and hold for 2 hours.

4. The method according to claim 1, characterized in that, In step 3, the mass ratio of BCNT to the volume of anhydrous ethanol is 5 mg: (10-20) mL, and the mass ratio of BCNT to polytetrafluoroethylene is 5:3; heating is carried out at 70°C.

5. The method according to claim 1, characterized in that, In step 4, the stainless steel mesh has a mesh size of 30-100, the polytetrafluoroethylene suspension has a concentration of 5 wt%, and the BCNT loading reaches 12.5 mg·cm⁻¹. -2 Anneal at 350℃.

6. The method according to claim 1, characterized in that, In step 5, the ratio of hexadecyltrimethylammonium bromide, ferric chloride hexahydrate, and deionized acetic acid is 54 mg: 200 mg: 68 mg: 0.3 mL: 15 mL, and the mass ratio of hexadecyltrimethylammonium bromide to 2-aminoterephthalic acid is 54 mg: 68 mg. The reaction is carried out hydrothermally at 110 °C.

7. A self-supporting gas membrane bladder three-phase interface stable gas diffusion electrode prepared by the method of any one of claims 1-6.

8. The application of a self-supporting gas film bladder three-phase interface stable gas diffusion electrode prepared by the method of any one of claims 1-6, characterized in that, As an application of cathodes in the degradation of organic pollutants, the organic pollutants are acetaminophen, tetracycline, sulfadiazine, phenols, naproxen, carbamazepine, atrazine, and chloramphenicol.

9. An electro-Fenton water treatment method for degrading organic pollutants in water, characterized in that, Includes the following steps: Using the composite membrane prepared by any one of claims 1-6 as the cathode, one side of the cathode is immersed in a reaction solution containing organic pollutants, and the other side of the cathode is in contact with oxygen or air, with a DSA electrode as the anode; a supporting electrolyte and ferrous salt are added to the reaction solution and the pH is adjusted to acidic to oxidize and degrade organic pollutants.

10. The method according to claim 9, characterized in that, The distance between the anode and cathode is 5 mm-20 mm; the supporting electrolyte is sodium sulfate, 0.1 mol·L⁻¹. -1 -0.01 mol·L -1 The pH was adjusted using dilute sulfuric acid, and the ferrous salt was ferrous sulfate, at a concentration of 0.1 mmol·L⁻¹. -1 .